Lilly's big day - Henkes, Kevin ([New York] : Greenwillow Books, 2006)
When her teacher announces that he is getting married, Lilly the mouse sets her heart on being the flower girl at his wedding.
Booklist starred.
Notable/Best Books (A.L.A.).
School Library Journal starred.
3.3
K-3
Keywords: Mice -- Juvenile fiction; Teachers -- Juvenile fiction; Weddings -- Juvenile fiction; Mice -- Fiction; Teachers -- Fiction; Weddings -- Fiction; Mice -- Fiction; Teachers -- Fiction; Weddings -- Fiction